Fostering Innovation Resilience in Craft SMES: The Role of Triple Helix Collaboration and Toe Readiness in Indonesia - Etwin Fibrianie Soeprapto; Sri Gunani Partiwi; Retno Widyaningrum; Andri Kurniawan (Jurnal Locus Penelitian dan Pengabdian, 2026)
This research investigates the interaction between Triple Helix capability, Technology–Organization–Environment (TOE) readiness, organizational ambidexterity, and organizational resilience in enhancing innovation performance and achieving sustainable competitive advantage among craft-based Small and Medium Enterprises (SMEs) in East Kalimantan, Indonesia. This study aims to examine the collective influence of TOE readiness, organizational ambidexterity, and organizational resilience on innovation performance, assess the direct impact of TOE readiness, and investigate the mediating roles of ambidexterity and resilience. A quantitative research approach was employed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with data collected from 154 SME respondents. The study assessed the measurement model’s validity and reliability, evaluated structural relationships, and applied Importance–Performance Map Analysis (IPMA) to identify strategic priorities for SME development. The results reveal that Triple Helix capability, TOE readiness, organizational ambidexterity, and organizational resilience significantly and positively influence SME innovation performance. TOE readiness acts as a complementary partial mediator between Triple Helix capability and innovation performance, while ambidextrous organization and resilience strengthen SMEs’ adaptive capacity in dynamic market environments. IPMA results highlight TOE readiness as the primary construct requiring improvement to enhance innovation outcomes. Findings emphasize the need for continuous collaboration between government, academia, and industry to strengthen digital readiness, promote innovation capability, and ensure sustainable SME competitiveness. This study contributes a comprehensive integrative model linking the Triple Helix framework with TOE readiness and internal organizational capabilities—an area still limited in developing-country SME contexts—offering both theoretical enrichment and practical strategies for sustainable innovation-driven growth.